Implementasi Fisher-Yates Shuffle pada Fitur Kuis dalam Media Pembelajaran EduBidan Berbasis Web (Studi Kasus: Mahasiswa Kebidanan Unsika) - Muhamad Ikhsan Rizqi Yanuar; Aries Suharso; Asep Jamaludin (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2026)
Midwifery education requires structured, flexible, and user-friendly digital media to support conceptual, procedural, and visual learning as well as assessments with varied question orders. This study develops EduBidan as a web-based Digital Midwifery LMS, analyzes Fisher-Yates Shuffle in evaluation quizzes, and evaluates functionality and usability. The system was developed using the Prototype method through five stages and three evaluation iterations. EduBidan supports Student, Lecturer, and Administrator roles with features for materials, quizzes, progress tracking, and grade summaries. Fisher-Yates Shuffle randomizes questions and answer options using a seed to maintain consistent arrangements for the same student and quiz. Testing included Black Box Testing, algorithm testing, and the System Usability Scale (SUS). All Black Box scenarios produced the expected results. Three algorithm-testing scenarios showed reordered items without missing or duplicated data, consistency after page reloads, and accurate scoring. SUS testing with 34 respondents produced a score of 84.41, grade B, an adjective rating of Excellent, and an acceptability range of Acceptable. The results indicate that EduBidan fulfills functional requirements, has good usability, and is acceptable to users.